Plasmodium falciparum and intestinal parasitic co-infections in HIV-infected patients in Benin City, Edo State, Nigeria - Frederick Olusegun Akinbo; Christopher Ehis Okaka; Richard Omoregie (Journal of Infection in Developing Countries)
Introduction: Human co-infection with Plasmodium falciparum and helminthes is ubiquitous throughout Africa. This study aimed to determine the co-infections of Plasmodium falciparum infection in HIV and intestinal parasitic infections, and their immunological distribution, in Benin City, Nigeria.